Incidental learning of second language vocabulary through reading for pleasure - Muthiah, Puvenesvary; Rao, Ravantharanathe (Universiti Utara Malaysia, 1996)
The major purpose of this study is to find out if incidental learning of words from context takes place as a result of minimum exposure through reading for pleasure. In this study, the experimental design incorporating the pre-and post-test procedure was employed. Convenient sampling was used to select the subjects of this study. The 16 subjects in this study are from the intermediate English course (BZ1032) of UUM. Only those with B+ and B grades in their BZ1022 course were selected because these grades seem to safely represent language proficiency at the intermediate level. The post-test results of the experimental group, as indicated by the descriptive statistics and the Mann-Whitney U Test, were superior to the results obtained by the control group. The subject who participated in the reading activity seemed to have learn the meanings of more words compared to those who did not. The findings of this study suggest that a reading for pleasure activity should be incorporated in the curriculum at institutions of higher learning to promote incidental vocabulary learning among students. The experience gained by the researchers also reveals that this is a practical approach to be implemented in the classroom since it can be easily carried out with minimum supervision.